Yoga in Britain: Stretching Spirituality and Educating Yogis, by Suzanne Newcomb. (2nd October 2019) - Miller, Christopher
Abstract : Yoga in Britain: Stretching Spirituality and Educating Yogis, by Suzanne Newcombe. Sheffield: Equinox, 2019. xiv + 309 pp., £75.00 / 100.00 (hb), £24.95 / 36.00 (pb). ISBN 978-1-78179-659-7 (hb), 978-1-78179-661-0 (pb).